Power Scales, Institutions and Territories: Oriented to Development Strategies - Brandão, Carlos Antônio (Organizações & Sociedade, 2014)
This essay summarizes the traditional and modern approaches regarding “space scales” in the development process. It aims to point out that such approaches, having different criteria about “the local", suggest very distinct public and private actions. Most of these approaches are theoretical explanations about very different situations, in historical and geographical terms. It is discussed how the theoretical and analytical handling should be inspired by a context and space scale conception, built politically and socially. The essay identifies some challenges generated by environrnents with extremely diverse structures, so common in Brazilian underdevelopment. Finally, it is presented a discussion about the “proper scale” to be used by institutions to reach social and economic development.